Pengaruh Model Pembelajaran Proyek dan Motivasi terhadap Kompetensi Praktik Pengelasan - Saerozi, Saerozi; Hadromi, Hadromi; Khumaedi, Khumaedi (Journal of Vocational and Career Education, 2017)
Penelitian ini bertujuan untuk mengetahui (1) Pengaruh model pembelajaran proyek berorientasi Ecopreneurship terhadap hasil belajar praktik pengelasan di SMK; (2) Pengaruh motivasi terhadap hasil belajar praktik pengelasan di SMK; (3) Pengaruh interaksi model pembelajaran proyek berorientasi Ecopreneurship dan motivasi belajar siswa secara bersama-sama terhadap hasil belajar praktik Pengelasan di SMK. Penelitian ini merupakan penelitian eksperimen dengan menggunakan teknik Simple Random sampling yang dilakukan kepada 60 siswa. Pengambilan data diperoleh melalui angket dan tes serta dianalisis menggunakan statistik deskriptif dan uji statistik anava dua jalan dengan interaksi. Hasil penelitian menunjukkan bahwa pada taraf signifikasi 5% : (1) Ada pengaruh penggunaan model pembelajaran proyek berorientasi Ecopreneurship terhadap hasil belajar praktik Pengelasan di SMK (2) Ada pengaruh motivasi belajar terhadap hasil belajar praktik pengelasan di SMK. (3) Ada pengaruh interaksi model pembelajaran proyek berorientasi Ecopreneurship dan motivasi belajar siswa secara bersama -sama terhadap hasil belajar praktik Pengelasan di SMK. This study is motivated by low of student activity, lack of understanding on environmental problem and non maximum learning outcome of welding practice in class X TKR students in Vocational High School. This study aims to determine (1) the effect of Ecopreneurship-oriented project learning model on the learning outcomes of welding practice in Vocational High School; (2) The effect of motivation on the learning outcomes of welding practice in Vocational High School; (3) The interaction effect of Ecopreneurship-oriented project learning model and student learning motivation simultaneously on learning outcomes of welding practice in Vocational High School. This study was an experimental study using Simple Random sampling technique performed to 60 students. The data were collected through questionnaire and test and analyzed using descriptive statistic and two ways ANOVA statistical test with interaction. The results showed that at 5% significance level: (1) There was an effect of Ecopreneurship-oriented project learning model on the learning outcomes of welding practice in Vocational High School (2) There was an effect of learning motivation on the learning outcomes of welding practice in Vocational High School. (3) There was an interaction effect of Ecopreneurship-oriented project learning model and student learning motivation simultaneously on learning outcomes of welding practice in Vocational High School. This study has an advantage to add insight about the learning model/strategy to improve student learning outcomes, as well as a contribution of scientific work for the development of useful science for society.